The 'Tribes' of Israel? a Bible Translator's Dilemma - Mojola, Aloo Osotsi (1998)
This article written from a Bible's translator's perspective takes issue with the way in which the use and translation of certain ethnic terms in the Hebrew Bible con tinues to distort the understanding of ancient pre-monarchic Israelite society. The dominance of models drawing from western-European systems is no doubt a con tributory factor. What kind of social entity is suggested by these terms? What in fact was the social character of ancient pre-monarchic Israelite society? The paper focuses attention on the problem of 'tribal identity' in pre-monarchic Israelite soci ety. A review of the complex process of 'retribalization' in the African context is taken as a basis for reflecting on the Israelite case. It is suggested that social pro cesses in some contemporary peasant societies offer useful insights for understand ing ancient societies. In conclusion a reinterpretation of ancient Israelite kinship terms as used in the Hebrew Bible is attempted.